Night Runner - Turner, Max 1971- (New York : St. Martin's Griffin, 2009)
Fifteen-year-old Zach is quite content living in a mental ward because of his unusual allergies until dark secrets about his past, his parents, and his strange sickness slowly surface, placing him in great danger.
Keywords: Vampires -- Fiction; Secrecy -- Fiction